Targeted Hybrid Nanocarriers as Co-Delivery Systems for Enhanced Cancer Therapy - Joan Onyebuchi Erebor; Elizabeth Oladoyin Agboluaje; Ava M. Perkins; Megha Krishnakumar; Ndidi Ngwuluka (Advanced Pharmaceutical Bulletin)
Hybrid nanocarriers have realized a growing interest in drug delivery research because of the potential of being able to treat, manage or cure diseases that previously had limited therapy or cure. Cancer is currently considered the second leading cause of death globally. This makes cancer therapy a major focus in terms of the need for efficacious and safe drug formulations that can be used to reduce the rate of morbidity and mortality globally. The major challenge encountered over the years with cancer chemotherapy is the non-selectivity of anticancer drugs, leading to severe adverse effects in patients. Multidrug resistance has also resulted in treatment failure in cancer chemotherapy over the years. Hybrid nanocarriers can be targeted to the site and offer co-delivery of two or more chemotherapeutics, thus leading to synergistic or additive results. This makes hybrid nanocarriers an extremely attractive type of drug delivery system for cancer therapy. Hybrid nanocarrier systems are also attracting attention as possible non-viral gene vectors that could have a higher level of transfection, and be efficacious, with the added advantage of being safer than viral vectors in clinical settings. An extensive review of various aspects of hybrid nanocarriers was discussed in this paper. It is envisaged that in the future, metastatic cancers, multi-drug resistant cancers, and low prognosis cancers like pancreatic cancers, will have a lasting solution via hybrid nanocarrier formulations with targeted co-delivery of therapeutics.